Paradigma Positivistik dalam Analisis Epistemologis Penggunaan Ekstrak Pakis sebagai Alternatif Pengendalian Parasit pada Udang Vaname - Putra Arif Yanto Umar; Hasim Hasim (Faculty of Science and Technology University Ibrahimy, 2025)
This study examines the application of the positivistic paradigm in epistemological analysis of fern extract utilization as an alternative parasite control method in vannamei shrimp (Litopenaeus vannamei). Through literature review and epistemological analysis, this research explores how the positivistic approach shapes understanding and validation of traditional knowledge about fern's antiparasitic properties in modern aquaculture science. The positivistic paradigm emphasizes empirical verification, measurable variables, and scientific objectivity in evaluating the effectiveness of fern extracts against shrimp parasites. Previous studies demonstrate that various fern species contain bioactive compounds such as flavonoids, tannins, and saponins that exhibit antiparasitic activity. The epistemological analysis reveals that the positivistic approach facilitates the transformation of traditional ecological knowledge into scientifically validated aquaculture practices through controlled experiments, statistical analysis, and replicable methodologies. However, this paradigm also presents limitations in capturing the holistic understanding of traditional knowledge systems. The integration of positivistic methods with indigenous knowledge systems offers promising pathways for developing sustainable and effective parasite management strategies in vannamei shrimp aquaculture.